Assessment of antimicrobial activity and methyl orange dye removal by Klebsiella pneumoniae-mediated silver nanoparticles - Desai Reema; Yadav Virendra Kumar; Patel Bhakti; Rami Esha; Almoallim Hesham Saleh; Ansari Mohammad Javed; Choudhary Nisha; Sahoo Dipak Kumar; Patel Ashish (Green Processing and Synthesis, 2024)
The synthesis of silver nanoparticles (AgNPs) using bacteria is more interesting because of their non-toxic, biocompatible, environmentally friendly, and cost-effectiveness. In the present research work, AgNPs were synthesized by Klebsiella pneumoniae in two steps: first, K. pneumoniae was grown in nutrient broth, followed by mixing of bacterial supernatant and silver nitrate aqueous solution in an optimized ratio. The synthesized AgNPs were thoroughly analyzed using analytical instruments for a detailed investigation. The absorption peak observed using UV-visible spectrophotometry at 464 nm indicated the development of AgNPs, while the characteristic bands for the AgNPs by infrared spectroscopy were observed in the region of 500–4,000 cm−1. Morphological examination via field emission SEM unveiled spherical-shaped AgNPs whose sizes varied from 22.25 to 47.99 nm, along with high aggregation. The crystallinity nature of the synthesized AgNPs was demonstrated by X-ray diffraction, which revealed major intensity peaks at 2θ values of 27.6°, 31.9°, and 46°. AgNPs showed 26.6% of methyl orange dye removal within 50 min. The antibacterial activities against Bacillus cereus, Bacillus megaterium, Serratia marcescens, and Staphylococcus aureus showed maximum zones of inhibition, i.e., 14 mm (10 mg·mL−1), 16 mm (5 and 10 mg·mL−1), 13 mm (5 and 10 mg·mL−1), and 12 mm (10 mg·mL−1). Therefore, the bacterial-synthesized AgNPs exhibited potential application in the field of biomedicine, which may be further used against various other pathogens.